Pneumatic press machine Rice bran oil Extractor for a Pilot scale and its potential for the SME Scale: Performance of Yield and Anthocyanin Content - Nugrahani, Ratri Ariatmi; Hendrawati, Tri Yuni; Hasyim, Ummul Habibah; Sari, Fatma; Saputra, Muhammad Ilham; Busratama, Afryan; Ramadhani, Annisyah (International Journal of Membrane Science and Technology, 2023)
: Rice is a food crop that serves as a source of energy. As an edible food, the rice skin is separated, which produces solid waste in the form of rice bran. Generally, the rice bran produced from the rice milling process is 8-12%. Rice bran is only used for animal feed. Rice bran contains various vitamins and antioxidants, one of which is anthocyanins. The benefits of anthocyanins include natural pH indicators, natural dyes usually used in food and beverages, and anticancer. Extraction in this study using a pneumatic press machine for pilot scale and the other aim of this research were study the potential of SME (small and medium enterprises) Scale. The analysis of rice bran oil is conducted by the Spectrophotometric method. The variables used in the extraction process in this study were pressures of 3, 4, 5, 6, and 7 bars and stabilization time of 8, 11, 14, 17 and 20 minutes with a pressure of 7 bar on the yield and the content of anthocyanins. The obtained yield is at the 7 bar, which was 6.45%. The yield shows that the pressure is related to the yield of rice bran oil. It shows that the highest anthocyanin content was obtained at the optimum stabilization time is 20 minutes with an anthocyanin content of 36.9 mg/kg. The capacity of this press machine is 5 kg, so by using the ratio of rice bran: solvent (1: 7), if the maximum raw material that can be processed is 625 gr and 4375 gr solvent, a yield of 40.3125 gr will be obtained. This value shows the potential for using a pneumatic press machine as a pilot scale extractor for SME (Small Medium Entreprise) needs